Penentuan Sektor Basis dan Strategi Pengembangan Sektor Non Basis di Kabupaten Banjar Tahun 2010-2018 - Muhammad Rizky Rifani; Sa’roni, Chairul (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
The purpose of this study is to (1) determine the base sector owned by the BanjarRegency, and (2) the non-base sector development strategy in Banjar District. Theanalysis method to determine the base sector is calculated through Location quotient,Shift Share, and Klassen Typology for development strategies through SWOT analysis.Using secondary data in the form of gross regional domestic product according toemployment at constant prices and primary data obtained from interviews withrespondents who are considered experts or know the situation. The results showed fourprimary sectors: construction sector, wholesale and retail trade sector, car andmotorcycle repair sector, accommodation and food and beverage supply sector, and theInformation and Communication sector. The industry that wants to be developed is theagriculture, forestry, and fisheries sectors that produce the strategy that best suits thesituation is the S-O strategy.